Work Discipline of Staff in Information Technology and Data Base Units - Ahmad Yani; Muhammad Munawir Pohan; Yogi Ahmad Yani; Ade Putra Hayat (International Journal of Social Science and Business, 2023)
Staff is responsible for ensuring that all regulations in an agency are followed. Due to indiscipline, work productivity frequently fails to reach work achievement targets. This study aims to reveal the work discipline of staff in the information technology unit and a database based on work output. This research was conducted using a qualitative method with a case study approach. The informants in this study were staff of the information technology unit and database, totalling three people. The researcher is the key instrument in collecting and interpreting the data in this study. The data collection techniques used were observation, interviews, and document studies. Data analysis techniques in this study using Nvivo Plus version 11 software include data input, coding, exploration, visualization, and presentation. This study found that staff work discipline was perfect, as evidenced by the online presence of incoming and outgoing hours on time. Timeliness in data reporting can be completed on time if all the data available in the Siakad application is fixed and complete. The target of achieving work output from Pddikti data reporting is still at 80%. There are still many obstacles and problems that occur in data reporting. Efforts to improve and evaluate work output in the form of Pddikti data reporting have been carried out by all parties.